How Much Binding Is the Bill? - Gianluca Cafiso; Roberto Cellini (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study whether and how much the interest bill conditions the size and composition of public expenditures. The group of EU 15 countries over the 1995-2016 period is the object of analysis. We study both total public expenditures and public expenditures by function of government in order to unveil which sectors are more responsive to an interest bill variation.
Keywords: H61; H62; H63; E62; E63; 330; interest bill; public expenditures; public debt